2014
DOI: 10.3844/jmssp.2014.267.274
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy Model Optimization for Time Series Data Using a Translation in the Extent of Mean Error

Abstract: Recently, many researchers in the field of writing about the prediction of stock price forecasting, electricity load demand and academic enrollment using fuzzy methods. However, in general, modeling does not consider the model position to actual data yet where it means that error is not been handled optimally. The error that is not managed well can reduce the accuracy of the forecasting. Therefore, the paper will discuss reducing error using model translation. The error that will be reduced is Mean Square Erro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The application of the fuzzy model in forecasting time series has widespread increasingly. The researchers have also been trying to improve the forecasting time series quality in many ways [2]. Song and Chisoom have studied the fuzzy application for the university ' 'enrolment's prediction [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The application of the fuzzy model in forecasting time series has widespread increasingly. The researchers have also been trying to improve the forecasting time series quality in many ways [2]. Song and Chisoom have studied the fuzzy application for the university ' 'enrolment's prediction [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…It has suggested that an idea of applying hybrid methods in place of AR in modelling subintervals is promising. Some of the approaches are fuzzy system as shown in work of Nurhayadi et al [34], [35] and neuro fuzzy as in Abadi et al [36].…”
Section: Arrival Time Of P and S Wave Of Mount Rinjanimentioning
confidence: 99%
“…The research on fuzzy system that uses time series data was first conducted by Song [5]- [7] to predict the number of enrollments in a university. Other research conducted by Nurhayadi [8] is to predict the register at the Albama University. Then, Shah [9] applied fuzzy time series to predict the gross domestic capital in In fact, Lee's research [16] weighted fuzzy time series method has better accuracy than Chen's [11], Yu's [12], and Cheng's [17] method.…”
Section: Introductionmentioning
confidence: 99%